Decline in renal function and oral anticoagulation dose reduction among patients with atrial fibrillation. Issue 5 (7th January 2020) - Inohara, Taku; Holmes, DaJuanicia N; Pieper, Karen; Blanco, Rosalia G; Allen, Larry A; Fonarow, Gregg C; Gersh, Bernard J; Hylek, Elaine M; Ezekowitz, Michael D; Kowey, Peter R; Reiffel, James A; Naccarelli, Gerald V; et al.
Abstract : Objective: Non-vitamin K oral anticoagulants (NOACs) require dose adjustment for renal function. We sought to investigate change in renal function over time in patients with atrial fibrillation (AF) and whether those on NOACs have appropriate dose adjustments according to its decline. Methods: We included patients with AF enrolled in the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation II registry treated with oral anticoagulation. Worsening renal function (WRF) was defined as a decrease of >20% in creatinine clearance (CrCl) from baseline. The US Food and Drug Administration (FDA)-approved package inserts were used to define the reduction criteria of NOACs dosing. Results: Among 6682 patients with AF from 220 sites (median age (25th, 75th): 72.0 years (65.0, 79.0); 57.1% male; median CrCl at baseline: 80.1 mL/min (57.4, 108.5)), 1543 patients (23.1%) experienced WRF with mean decline in CrCl during 2 year follow-up of −6.63 mL/min for NOACs and −6.16 mL/min for warfarin. Among 4120 patients on NOACs, 154 (3.7%) patients had a CrCl decline sufficient to warrant FDA-recommended dose reductions. Of these, NOACs dosing was appropriately reduced in only 31 (20.1%) patients. Compared with patients with appropriately reduced NOACs, those without were more likely to experience bleeding complications (major bleeding: 1.7% vs 0%; bleeding hospitalisation: 2.6% vs 0%) at 1 year. Conclusions: In the US practice, about one-fourth of patients with AF had >20% decline in CrCl over time during 2 year follow-up. As a result, about 3.7% of those treated with NOACs met guideline criteria for dose reduction, but of these, only 20.1% actually had a reduction.